Pengaruh Status Sosial Dan Keadaan Lingkungan Masyarakat Terhadap Minat Siswa SMA Swasta Melanjutkan Ke Perguruan Tinggi di Kabupaten Ogan Komering Ilir - Mambora, Moch; Harapan, Edi; Nurlina, Nurlina (Universitas Riau, 2023)
The lack of interest in this subject is the issue in private high school students continuing their education at tertiary institutions. The number demonstrates this of private high schools at Ogan Komering Ilir district in 2021, where 67% will continue on to the world of work and 33% will continue on to the higher education level. tall. This study seeks to fill that gap by investigating and determining the impact of social status and environmental conditions on the interest of private high school students in Ogan Komering Ilir Regency in carrying out their tertiary-level education. Quantitative research methodology was applied for the study. Data regarding the effect of changing social status and environmental conditions in the community on the interest of private high school students in continuing on to tertiary institutions is presented in the form of quantitative data, which is analysed using parametric statistics. The research subject was 696 people, and the number of samples representing the research subjects was 248 people. Of these 248 people, 20–30 people per school will be randomly selected from each school. The research results obtained a correlation between social status (X1) and environmental conditions (X2), together with the interests of private high school students in Ogan Komering Ilir Regency. This value indicates the relationship category